Investigation of Retinal Microcirculation in Diabetic Patients Using Adaptive Optics Ophthalmoscopy and Optical Coherence Angiography - Florian Baltă; Irina-Elena Cristescu; Andrada-Elena Mirescu; George Baltă; Mihail Zemba; Ioana Teodora Tofolean (Journal of Diabetes Research)
The current research approaches the retinal microvasculature of healthy volunteers (17 subjects), patients with diabetes mellitus without retinopathy (19 subjects), and of diabetic patients with nonproliferative (17 subjects) and proliferative (21 subjects) diabetic retinopathy, by using adaptive optics ophthalmoscopy and optical coherence ophthalmoscopy angiography. For each imaging technique, several vascular parameters have been calculated in order to achieve a comparative analysis of these imaging biomarkers between the four studied groups. The results suggest that diabetic patients with or without diabetic retinopathy prove signs of retinal arteriole structural alterations, mainly showed by altered values of wall to lumen ratio, calculated for the superior or inferior temporal branch of the central retinal artery, near the optic nerve head, and significant changes of the vascular density in the retinal superficial capillary plexus. Both adaptive optics ophthalmoscopy and optical coherence ophthalmoscopy angiography are providing useful information about the retinal microvasculature from early onset of diabetic disease, having a promising diagnostic and prognostic role in the future.